Long‐term safety and efficacy of add‐on cannabidiol in patients with Lennox–Gastaut syndrome: Results of a long‐term open‐label extension trial. (20th July 2021) - Patel, Anup D.; Mazurkiewicz‐Bełdzińska, Maria; Chin, Richard F.; Gil‐Nagel, Antonio; Gunning, Boudewijn; Halford, Jonathan J.; Mitchell, Wendy; Scott Perry, Michael; Thiele, Elizabeth A.; Weinstock, Arie; Dunayevich, Eduardo; Checketts, Daniel; et al.
Summary: Objective: Lennox–Gastaut syndrome (LGS) is an epileptic encephalopathy that is often treatment resistant. Efficacy and safety of add‐on cannabidiol (CBD) to treat seizures associated with LGS was demonstrated in two randomized controlled trials (RCTs). Patients who completed the RCTs were invited to enroll in this long‐term open‐label extension (OLE) trial, GWPCARE5 (NCT02224573). We present the final analysis of safety and efficacy outcomes from GWPCARE5. Methods: Patients received plant‐derived highly purified CBD (Epidiolex in the United States; Epidyolex in the European Union; 100 mg/ml oral solution), titrated to a target maintenance dose of 20 mg/kg/day over 2 weeks. Based on response and tolerability, CBD could then be reduced or increased up to 30 mg/kg/day. Results: Of 368 patients with LGS who completed the RCTs, 366 (99.5%) enrolled in this OLE. Median and mean treatment duration were 1090 and 826 days (range = 3–1421), respectively, with a mean modal dose of 24 mg/kg/day. Adverse events (AEs) occurred in 96% of patients, serious AEs in 42%, and AE‐related discontinuations in 12%. Common AEs were convulsion (39%), diarrhea (38%), pyrexia (34%), and somnolence (29%). Fifty‐five (15%) patients experienced liver transaminase elevations more than three times the upper limit of normal; 40 (73%) were taking concomitant valproic acid. Median percent reductions from baseline ranged 48%–71% for drop seizures and 48%–68% for total seizures through 156 weeks. Across all 12‐week visit windows, 87% or more of patients/caregivers reported improvement in the patient's overall condition on the Subject/Caregiver Global Impression of Change scale. Significance: Long‐term add‐on CBD treatment had a similar safety profile as in the original RCTs. Sustained reductions in drop and total seizure frequency were observed for up to 156 weeks, demonstrating long‐term benefits of CBD treatment for patients with LGS.